The Implications of Transformational Leadership Styles, Organizational Commitments and Teamwork Performance Among Law Enforcement in Malaysia - Hj Mohd, Azmi; Nisa Mohd Arshad, Khairun (KnE Social Sciences, 2019)
The purpose of this study is to examine and evaluate the implications of organizational commitment factors as a mediator of the relationship between transformational leadership styles and teamwork performance among law enforcement in Malaysia. Quantitative research design has been used which comprise a number of 254 support group of law enforcement officers in the Federal Territory of Putrajaya. Multiple regression analysis is used to evaluate the direct and indirect relationships of variables and study models. The two factors characteristic of the transformational leadership style are used as an independent variable in looking at the effectiveness of teamwork performance among law enforcement. The inspirational motivation and individual considerations have positive and significant relationships with teamwork performance. Organizational commitment is found to have a partial mediator that influenced the relationship between inspirational motivation and individual consideration in teamwork performance. The inspirational, motivational features and individualized considerations in the style of transformational leadership are necessary and emphasized in producing more productive and effective teamwork commitments and performance. This study presents the details of the implications of transformational leadership style characteristics on organizational commitment and teamwork performance in the context of law enforcement in Malaysia.